2013
DOI: 10.1093/ntr/ntt203
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Exposure to Vapors From Electronic Cigarettes

Abstract: Using an e-cigarette in indoor environments may involuntarily expose nonusers to nicotine but not to toxic tobacco-specific combustion products. More research is needed to evaluate health consequences of secondhand exposure to nicotine, especially among vulnerable populations, including children, pregnant women, and people with cardiovascular conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
281
2
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(305 citation statements)
references
References 21 publications
(25 reference statements)
12
281
2
10
Order By: Relevance
“…4 These include polycyclic aromatic hydrocarbons 32 as well as nicotine, volatile organic compounds, ultrafine particles, and particulate matter. [32][33][34] Metal and silicate particles, some of which occur at higher levels than in conventional cigarettes, have also been detected in ENDS aerosol. 35,36 Thirdhand aerosol, as with thirdhand smoke, is the residual aerosol that remains on surfaces and in dust after ENDS use; this residual may react with oxidants in the environment to yield secondary pollutants or be reemitted into the gas phase.…”
Section: Ends Secondhand and Thirdhand Aerosolmentioning
confidence: 99%
“…4 These include polycyclic aromatic hydrocarbons 32 as well as nicotine, volatile organic compounds, ultrafine particles, and particulate matter. [32][33][34] Metal and silicate particles, some of which occur at higher levels than in conventional cigarettes, have also been detected in ENDS aerosol. 35,36 Thirdhand aerosol, as with thirdhand smoke, is the residual aerosol that remains on surfaces and in dust after ENDS use; this residual may react with oxidants in the environment to yield secondary pollutants or be reemitted into the gas phase.…”
Section: Ends Secondhand and Thirdhand Aerosolmentioning
confidence: 99%
“…1 The liquid solution (referred to as ''e-liquid'') is typically composed of propylene glycol, glycerin, flavouring and nicotine. 2,3,4 Unlike cigarettes, e-cigarettes do not produce side-stream smoke, 5 and exposure studies suggest that they do not contain the same levels of harmful chemicals that cigarettes do. 2,4,5,6 However, the vapours…”
Section: Introductionmentioning
confidence: 99%
“…25 Contrarily, Czoguli et al reported lower nicotine concentrations in the air when using e-cigarettes, compared to traditional ones. 26 To date, e-cigarette use by teenagers, and even children, is a major concern. A survey conducted by Goniewicz et al among Polish teenagers between 15 and 19 years old presented a successive increase in the prevalence of e-smoking.…”
Section: Discussionmentioning
confidence: 99%